Demystifying the Social Pathology in the Animated Movie ‘Barbie as the Princess and the Pauper (2004)’ Through Literary Sociology Theory - Hayati, Kemala Diah Tri; Nurhayati, Sulasih (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2025)
The animated movie Barbie as the Princess and the Pauper (2004) shows a conflict between characters who demonstrate inappropriate behaviour and are contrary to social norms. The article aims to demystify the representation of several social pathology acts and the impact of these actions using a qualitative method through a Sociology of Literature approach by Alan Swingewood. Furthermore, this article also employs a cinematography theory approach (mise-en-scene) to identify elements of social pathology based on camera movements, character expressions, costumes, and location settings in the movie. The article finds several forms of social pathologies, such as theft, extortion, animal abuse, and abduction, which lead to the kingdom’s bankruptcy, the mistreatment of animals, restrictions on rights, and anxiety among the families of those affected. It can be concluded that the animated movie provides an overview of social pathology forms using the sociology of literature theory, making it suitable for education and self-awareness among a wider audience about real-life criminality.